Conceptual Metaphor in Lonestar Song Lyrics “I’m Already There”: A Cognitive Stylistic Analysis - Atikah Auni Nasution; Desna Uli Matanari; Afiqah Fianda; Rheina Sasmita; Rahmadsyah Rangkuti (LPPM Universitas Bumigora Mataram, 2024)
Metaphor is one of the most effective strategies for making literary works more evocative, striking, and beautiful. Metaphor's significance goes beyond literature to cognitive stylistics, which studies the cognitive processes that underpin language use and interpretation. This study aims to explain the types of conceptual metaphors found in the Lonestar song lyrics